Disturbance Rejection Problem with Stability By Static Output Feedback Of Linear Continuous Time System - Soleha (Pusat Publikasi Ilmiah LPPM Institut Teknologi Sepuluh Nopember, 2006)
Disturbance rejection problem with stability by static output feedback of linear-time invariant continuous time system is solvable if there is found a static output feedback control law, u(t) = Ky(t) (if possible), such that disturbance q(t) has no in°uence in controlled output z(t). So, it is needed the necessary and su±cient condition disturbance rejection problem is solvable. By using the definition and characteristics of (A, B)-invariant subspace, and (C, A)-invariant subspace, then it will be find the necessary and su±cient condition disturbance rejection problem of that system will be solved if and only if maximal element of a set of (C, A)-invariant is an (A, B)-invariant subspace that internally stabilizable and externally stabilizable.